The Church, Digital Technology and Media: A Biblical Reflection on Romans 8:19-23 - Ernest Nyarko (Noyam Journals, 2023)
This paper seeks to shed light on the author's perspective as far as the interplay between the church especially in Ghana, digital technology, and media is concerned. The study was done mainly through literary activity in existing sources from Biblical and materials on technology and media. It employed such methodological tools as descriptive and theological in discussing the subject at hand. It briefly looked at the basic meaning of the church. It then continued by highlighting what technology and media are and discussed how the church, especially in Ghana, can use them in these contemporary times. Through some biblical passages, the study demonstrated that technology and media are part of God's creation. However, since technology and media are products of human ingenuity and natural resources, they like other creations as Paul argues in the selected passage (Rom. 8:19-23), are also subject to the present corruption of the creation as a result of sin or futility. In other words, technology and media are not excluded from the effects of humanity's fall into sin. They are also groaning from the pain of sin and waiting eagerly for their redemption from the bondage of decay.